QUALITY FACTORS IN THE CONCEPT DEVELOPMENT AND MANAGEMENT DECISIONS - M. Yu. Kuzmin (Модернизация, инновация, развитие)
The article is devoted to the concept of quality factors of development and decision-making. The quality of management decisions – this is theextent to which management decisions for your organization. The article shows that the choice of effective managerial decisions made within acertain measure of its quality system, when the alternatives are formulated and carried out their comparative evaluation.